Eksplorasi Implementasi Infographic Project pada Pembelajaran Statistika dalam Mengembangkan Kemampuan Representasi dan Interpretasi Data Siswa Kelas X - Febriani, Rini; El Walida, Sikky (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2025)
Statistics learning plays an important role in developing students’ data literacy, particularly their abilities in data representation and interpretation. However, statistics instruction at the secondary school level remains largely procedural, providing limited opportunities for students to understand data contextually. This study aims to explore the implementation of an infographic project in statistics learning and to examine the development of Grade X students’ data representation and interpretation skills. This research employed a qualitative approach with an exploratory design. The research subjects consisted of one group of four Grade X students at Madrasah Aliyah Negeri Sampang. Data were collected through classroom observation, semi-structured interviews, and analysis of students’ infographic artifacts. Data analysis involved data reduction, data display, and conclusion drawing, with validity ensured through technique and source triangulation. The results indicate that the infographic project supports students in representing data in various visual forms and interpreting data by identifying patterns, comparisons, and contextual meanings. These findings suggest that the infographic project has the potential to serve as an alternative approach to statistics learning that promotes active student engagement and the development of data literacy skills.